Climate risk, bank lending and monetary policy - Carlo Altavilla; Miguel Boucinha; Marco Pagano; Andrea Polo (European Central Bank (ECB), 2024)
Combining euro-area credit register and carbon emission data, we provide evidence of a climate risk-taking channel in banks' lending policies. Banks charge higher interest rates to firms featuring greater carbon emissions, and lower rates to firms committing to lower emissions, controlling for their probability of default. Both effects are larger for banks committed to decarbonization. Consistently with the risk-taking channel of monetary policy, tighter policy induces banks to increase both credit risk premia and carbon emission premia, and reduce lending to high emission firms more than to low emission ones. While restrictive monetary policy increases the cost of credit and reduces lending to all firms, its contractionary effect is milder for firms with low emissions and those that commit to decarbonization.
Keywords: E52; G21; Q52; Q53; Q54; Q58; 330; climate risk; carbon emissions; interest rate; lending; monetary policy